2021
DOI: 10.1371/journal.pone.0247242
|View full text |Cite
|
Sign up to set email alerts
|

New methods for quantifying rapidity of action potential onset differentiate neuron types

Abstract: Two new methods for quantifying the rapidity of action potential onset have lower relative standard deviations and better distinguish neuron cell types than current methods. Action potentials (APs) in most central mammalian neurons exhibit sharp onset dynamics. The main views explaining such an abrupt onset differ. Some studies suggest sharp onsets reflect cooperative sodium channels activation, while others suggest they reflect AP backpropagation from the axon initial segment. However, AP onset rapidity is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…The AP parameters were extracted and evaluated from 20 RS and FS somatosensory cortical neurons stimulated via the current clamp, step-and-hold, and frozen noise stimulation paradigms (Figure 2). The rapidity, threshold, amplitude, and width of each neuron type's APs of the first 50 neuronal responses were averaged and contrasted across neuron types and stimulation methods (see Table 1 that the IFWd is a more consistent and reliable method for quantifying AP rapidity than the phase slope method [24]. Thus, AP rapidity refers to the rapidity calculated using the IFWd method throughout this paper.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AP parameters were extracted and evaluated from 20 RS and FS somatosensory cortical neurons stimulated via the current clamp, step-and-hold, and frozen noise stimulation paradigms (Figure 2). The rapidity, threshold, amplitude, and width of each neuron type's APs of the first 50 neuronal responses were averaged and contrasted across neuron types and stimulation methods (see Table 1 that the IFWd is a more consistent and reliable method for quantifying AP rapidity than the phase slope method [24]. Thus, AP rapidity refers to the rapidity calculated using the IFWd method throughout this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Five parameters were calculated for each spike. AP rapidity was calculated using two methods: the inverse full width at half maximum of the 𝑉 peak (IFWd ; [24,25]), and the phase slope method [16]. Notably, a recent previous study conducted by our team showed The frozen noise stimulus is the product of an artificial neural network that mimics post-synaptic current (for more details on frozen noise stimulus see reference [23]).…”
Section: Ap Parameters Quantificationmentioning
confidence: 99%
See 1 more Smart Citation